Quantitative assessment of bioactive compounds and the antioxidant activity of 15 jujube cultivars. (15th April 2015) - Kou, Xiaohong; Chen, Qiong; Li, Xianhua; Li, Mianfang; Kan, Cong; Chen, Boru; Zhang, Ying; Xue, Zhaohui
Highlights: Polysaccharides and total triterpenes are firstly compared in 15 red fresh jujubes. TOPSIS method is employed to comprehensively evaluate the nutrition of 15 jujubes. Bound polyphenols are detected firstly in jujube fruit. Abstract: Fifteen jujube cultivars late in their maturation were analysed in the red stage for bioactive compounds; including total phenolics (bound/free), total flavonoids, total polysaccharides, ascorbic acid, total triterpenes, proanthocyanidins and cyclic adenosine monophosphate (cAMP). The antioxidant activity was evaluated using the 2, 2-diphenyl-1-picrylhydracyl (DPPH ) and 2, 2′-azinobis (3-ethylbenzothiazoline-6-sulfonicacid) (ABTS + ) scavenging methods and the ferric reducing antioxidant power (FRAP) assay. The Order Performance by Similarity to Ideal Solution method (TOPSIS) was employed to evaluate the nutrition of different jujube cultivars based on their bioactive compounds. The results indicated that the contents of bioactive compounds and antioxidant capacities vary between different jujube cultivars. Correlation analysis revealed that ascorbic acid, polyphenols and proanthocyanidins were the 3 main components responsible for the antioxidant activity of jujubes. TOPSIS analysis indicated that Zyzyphus jujube cv. Nanjingyazao ranks the highest of the 15 jujube fruits with regards to nutritional value.